Stabilität und Variabilität mobilitätsbezogener Alltagshandlungen - eine qualitative soziale Netzwerkanalyse - Puhe, Maike (Schriftenreihe / Institut für Verkehrswesen, Karlsruher Institut für Technologie, 2023)
In order to understand the potential for change and persistence in everyday mobility-related practices, this book highlights the importance of social relationships in people's lives, such as with friends and family members, but also with work, sports clubs or shopping centres. Particular emphasis is placed on destination choices. The findings contribute to a conceptual model of destination choice that can be used in future transport demand models.